Updated transient gene expression protocol in Expi293F cells using PEI - Hederoth, Gustaf; de la Rosa, Andrés; Godec, Ana; Aguilar, Ximena; Napoleone, Antonino; Petrovic, Alex; Metzendorf, Nicole G.; Hultqvist, Greta (Frontiers in Bioengineering and Biotechnology, 2025)
Transient gene expression (TGE) is commonly used for the rapid production of protein-based therapeutics, including antibodies that require post-translational modifications. We previously published a protocol for efficient and cost-effective TGE of multispecific and multivalent antibodies. Here, we describe an optimized version of this protocol with key improvements in cost, workflow speed, and production capacity. First, the expensive Expi293 expression medium was replaced with BalanCD HEK293 medium, resulting in a substantial decrease in medium-related costs by approximately 90%. The addition of Pluronic F-68 was omitted, as the new medium already contains a similar surfactant. To minimize plasmid DNA usage, salmon sperm DNA was included as filler DNA during transfection, enabling a significant reduction in plasmid DNA input without compromising antibody yield. Second, the harvesting procedure was shortened from 2.5 h to just 15 min by adding the mineral compound diatomaceous earth (Celpure®) to the culture supernatant. This effectively absorbs and sequesters cells and debris, allowing rapid filtration without filter clogging or the previously required 1-h centrifugation step. Finally, we recommend high-flow rate HiScreen Fibro PrismA columns to further accelerate downstream antibody purification. Together, these improvements streamline the TGE workflow in Expi293F cells, enhance scalability, and increase throughput while maintaining efficiency in antibody production.